Spatial Variations in E-Commerce and its Impact on Urban Commercial Activities in Kirkuk Province - Abdulhasasn Jolan , Assist. Lect . Alaa (Basra studies journal, 2026)
This study examines spatial variation in e-shopping across Kirkuk City and its impact on urban retail activity using field surveys and composite indices. The findings reveal clear differences between neighborhoods and strong sectoral variation. Clothing and electronics were the most affected sectors. Retailers reported sales decreases of 62% in clothing and 58% in electronics. while Groceries remained relatively stable, with 24% reporting decreased sales and 56% reporting stable sales. Service activities also remained stable, with 61% reporting stability and 21% reporting increases. Restaurants showed a shift from in-store sales to delivery. About 57% of restaurant owners reported increased delivery orders. In contrast, 49% reported a decline in in-store sales. Overall, the impact of e-shopping is spatially and sector-ally selected for highlighting the need to strengthen hybrid retail and digital adaptation.